CALCULATION OF SOIL RETAINING WALL TYPE OF COUNTERFORT LANDSLIDES AT PROJECT MANAGEMENT ROAD SECTIONS POINT II SPONTAN KABUPATEN KUTAI KARTANEGARA - SYAH, JOHAN (KURVA S JURNAL MAHASISWA, 2014)
Landslides are displacement slope form of rock-forming material, material destruction, soil, or the mixture of materials, moving down the slopes or out. The occurrence of landslides caused by the presence of water that seep into the soil and add weight to the ground. If water penetrates the soil acts as a watertight sliding plane, the ground becomes slippery and soil weathering on it will move to follow the slope and off the slopes.Spontaneous road section II is the only access that connects the two regions Spontaneous with Tenggarong City, so in case of avalanches on the road, it can cause Spontaneous isolated region. Landslide that occurred on roads in the form of sliding of the road that could potentially lead to these roads cut off, so we need a swift and appropriate action in dealing with avalanche that happened on these roads.From the calculation results can be concluded that, dimensional wall pehanan high ground is 3 meters and a width of 1 meter, 1 meter thick plate with a length of 10 meters per segment review. Secure the stability of a retaining wall to bolster however affect the shear, so that the necessary foundation piles with additional bracing to the pile group to rigidify the structure of the walls and the pile.